2020
DOI: 10.1007/978-3-030-45691-7_44
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Peer-to-Peer Lending Secondary Market: What Determines the Successful Trade of a Loan Note?

Abstract: Predicting loan default in peer-to-peer (P2P) lending has been a widely researched topic in recent years. While one can identify a large number of contributions predicting loan default on primary market of P2P platforms, there is a lack of research regarding the assessment of analytical methods on secondary market transactions. Reselling investments offers a valuable alternative to investors in P2P market to increase their profit and to diversify. In this article, we apply machine learning algorithms to build … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, it was concluded that the trading volume is too small to meet the arbitrary conditions. Byanjankar et al (2020) proved, with empirical analysis, that the discount rate and number of days in default significantly impact an investor's decision. Reher (2014) highlighted the relation between the implementation of a secondary market and the level of interest rates in the primary market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was concluded that the trading volume is too small to meet the arbitrary conditions. Byanjankar et al (2020) proved, with empirical analysis, that the discount rate and number of days in default significantly impact an investor's decision. Reher (2014) highlighted the relation between the implementation of a secondary market and the level of interest rates in the primary market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reher (2014) highlighted the relation between the implementation of a secondary market and the level of interest rates in the primary market. According to an empirical study performed by Byanjankar et al (2020), this kind of expansion lowers interest rates and can have a risk impact on the main market. This paper's purpose is to add to the research that examines the secondary market in social lending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to an empirical study performed by Byanjankar et al (2020), this kind of expansion lowers interest rates and can have a risk impact on the main market. This paper's purpose is to add to the research that examines the secondary market in social lending.…”
Section: Literature Reviewmentioning
confidence: 99%